INTERDEPENDENSI ANTARA KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN KEPUTUSAN DIVIDEN - Linda Purnamasari; Sri Lestari Kurniawati; Melliza Silvi (Jurnal Keuangan dan Perbankan, 2009)
This paper examined a comprehensive test of the interdependencies amonginvestment decisions, financing decisions and dividend decisions. Three simultaneous equationmodels were used. By applying Two Stage Least Square (2-SLS) technique to 122 firms listed onIndonesian Stock Exchange, it was found out that there was no significant interdepenciesamong firms investment decisions, financing decisions and dividend decisions. Our resultsuggested the causality flow between firms investment decisions and dividend decisions wasbidirectional and positive, the causality flow between investment and financing decisions wasbidirectional and positive, while the causality flow between financing and dividend decisionswas bidirectional and negative.